(untitled) (Research, Society and Development, 2025)
The objective of this study is to evaluate the biodegradability of PLA biocomposites reinforced with banana fibers under different conditions, aiming to encourage the reduction of synthetic raw materials through the valorization of agro-industrial waste. One of the main environmental impacts of large-scale industrial production is the generation of synthetic waste that is difficult to degrade. In this context, the development of new materials obtained from natural raw materials has gained prominence in recent decades, seeking to reduce the negative effects associated with conventional production processes and promote more sustainable practices in the industry. In order to present a sustainable and biodegradable material, this study developed a polymeric composite reinforced with banana fiber, an agro-industrial residue. Banana fibers, both treated and untreated (in natura), were incorporated into a PLA polymeric matrix at 5% and 10% compositions via the extrusion process to obtain the biocomposites. The biodegradability test was performed following ASTM 71 D6003 and ASTM G160 standards in prepared organic soil, where the biocomposites were buried for 30, 60, and 90 days. Degradation analysis was performed by macroscopic evaluation, and mass loss by weighing. The composite that presented the highest degradation rate was the one reinforced with 10% fiber treated for 1.5 h. The results demonstrate that the incorporation of banana fibers increases mass loss in the composite, indicating an influence on accelerating the degradation of the composite in controlled soil.